Designing for change: Closing the action gap. (10th April 2023) - Finn, Steven M.
Food is central and critical to all that we do, and yet today's global food system is operating in unsustainable fashion – failing to adequately feed billions while simultaneously exceeding planetary boundaries. Further, in fewer than thirty years the world will need to provide sufficient nutrition for an additional 2 billion citizens with far less environmental impact – arguably the ultimate challenge of needing to do more with less. We are well aware that the food system must undergo transformational change to meet this challenge, but the pace of change remains insufficient. There is substantial opportunity for designers to play a key role in closing the knowledge-action gap and driving the needed change to a sustainable, equitable food system.